Casa del arbol, casa rojita, diminuta ratoncita marroncita - Godwin, Jane, 1964-; Canetti, Yanitzia, 1967-; Gomez, Blanca, 1978- (New York : Dial Books for Young Readers, 2019)
In this rhyming story, a young mouse makes her way around the world, introducing colors.
"Dolly Parton's Imagination Library"--Cover.
Bilingual text in English and Spanish.
Keywords: Color -- Juvenile fiction; Mice -- Juvenile fiction; picture books; Animal fiction; Fiction; Juvenile works; Picture books; Stories in rhyme; Stories in rhyme; Animal fiction; Picture books; Histoires rimes; Livres d'images.